2017
DOI: 10.1007/s11661-017-4316-2
|View full text |Cite
|
Sign up to set email alerts
|

Widening of Laths in Bainite

Abstract: Units of bainite in Fe-C alloys from the upper temperature range inherit their shape from Widmansta¨tten plates of ferrite, which are lathlike. The thickness increases by long-range diffusion of carbon and the length by short-range diffusion of carbon from the advancing edge of the tip. Both have been studied extensively and are fairly well understood. Widening growth seems to have been much neglected, but a study of some aspects of widening is now presented. The present report is the last one in a series of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
2
1
0
Order By: Relevance
“…It can also be noted that if N-W would have been used, which have 12 possible crystallographic orientations, variant pairs belonging to the same Bain group in the present work instead should have been considered as a single variant. The shift in misorientation within the ferrite plates in the same packet has previously been presented by Yin et al [14] where it was described as a rotation of the bainitic plate during widening. It is also noted that there is a deviation from the theoretical and experimental misorientation angles for V1-V4, V1-V8 and V1-V6, decreasing with increasing temperature, see Table III, as previously reported.…”
Section: A Temperature Dependence Of the Variant Pairingsupporting
confidence: 67%
See 1 more Smart Citation
“…It can also be noted that if N-W would have been used, which have 12 possible crystallographic orientations, variant pairs belonging to the same Bain group in the present work instead should have been considered as a single variant. The shift in misorientation within the ferrite plates in the same packet has previously been presented by Yin et al [14] where it was described as a rotation of the bainitic plate during widening. It is also noted that there is a deviation from the theoretical and experimental misorientation angles for V1-V4, V1-V8 and V1-V6, decreasing with increasing temperature, see Table III, as previously reported.…”
Section: A Temperature Dependence Of the Variant Pairingsupporting
confidence: 67%
“…The bainitic ferrite formed will thus, according to this hypothesis, be supersaturated with carbon from which carbides can form within the ferrite or if the formation of carbides is prevented by e.g., a Si addition, the carbon will diffuse into the residual austenite. [7,8,11] On the other hand, according to the diffusional hypothesis the first stage of the bainitic transformation occurs through the formation of thin bainitic ferrite plates that grow parallel to each other, constituting a packet, [13][14][15] while the second stage can be regarded as an eutectoid transformation, which can be either cooperative or degenerate in its nature as discussed by Hillert, [1,16] Aronson [17] and more recently by Yin et al [13] The cooperative eutectoid growth is characterized by ferrite and cementite growing together forming a lamellar structure if the carbon content is high enough. They grow preferentially at an angle to the primary ferritic plate and, moreover, both ferrite and cementite are in contact with the parent austenite during growth.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16] However, the microstructural difference observed at intermediate austempering temperatures correspond well to the observed difference in variant pairing with no clear dominant variant pair even if a slight increase in V1-V2 can be observed for the three steels with higher carbon content. Even if the complexity at the intermediate temperatures not is fully understood nor the mechanisms behind it, it is here clearly shown that all the changes in the bainitic microstructure appears gradually with austempering temperature which is consistent with Yin et al [24,42,44,45] Thus, definitions such as upper and lower bainite is not sufficient to describe the bainite structure over the full austempering temperature range since there is a region in-between that needs to be addressed. Further, a comparison between earlier published data and the data presented within this work was made by comparing the deviation angle for CPP and CPD between austenite and ferrite, Figure 7(a).…”
Section: Resultssupporting
confidence: 78%